2021
DOI: 10.1007/s10578-021-01214-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reflective Functioning as a Moderator for the Relationship Between Maternal Depression and Child Internalizing and Externalizing Problems

Abstract: Parental Reflective Functioning (PRF) refers to parents’ capacity to view their child’s and their own behavior considering inner mental states, like thoughts, desires, and intentions. This study’s objective was to examine whether PRF acted as a moderator for the relationships between maternal depression and child internalizing and externalizing problems. The sample was comprised of 685 Iranian mothers with preschoolers (3 to 5 years old) and school-aged (6–10 years old) children. To assess PRF, the PRF questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Although the ATTACH TM intervention is not primarily designed to improve parental depression, the observed trends that were observed are encouraging and supported by existing research. Parental RF has been negatively affected by higher severity of depressive symptoms [ 79 ], meaning that high depression scores negatively impact the ability to mentalize [ 80 ] and a significant negative correlation was observed between low RF and parental sensitivity ( r = −0.24, p = 0.048) [ 79 , 81 ]. Both parental RF and depression may play related roles in undermining maternal sensitive responsiveness and may influence child attachment security [ 32 , 33 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the ATTACH TM intervention is not primarily designed to improve parental depression, the observed trends that were observed are encouraging and supported by existing research. Parental RF has been negatively affected by higher severity of depressive symptoms [ 79 ], meaning that high depression scores negatively impact the ability to mentalize [ 80 ] and a significant negative correlation was observed between low RF and parental sensitivity ( r = −0.24, p = 0.048) [ 79 , 81 ]. Both parental RF and depression may play related roles in undermining maternal sensitive responsiveness and may influence child attachment security [ 32 , 33 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a central focus on the parent–child relationship, COS promotes the development of a secure attachment by supporting parents to function as a secure base and safe haven for their child (Parolin & Simonelli, 2016). The program aims to increase parental reflective functioning (RF), the parent's ability to understand their own and their child's observable behavior by considering intentions and emotions (i.e., internal, unobservable states; (Khoshroo & Seyed Mousavi, 2021; Suchman et al, 2011). Parental RF has implications for child development and attachment and is considered especially important in parents of infants and young children who are developmentally unable to describe their internal states to others and are reliant on co-regulation with caregivers (see Slade, 2005, for a review).…”
Section: The Case Of “Olivia”mentioning
confidence: 99%
“…Parental RF has implications for child development and attachment and is considered especially important in parents of infants and young children who are developmentally unable to describe their internal states to others and are reliant on co-regulation with caregivers (see Slade, 2005, for a review). One measure of Parental RF, the Parental Reflective Functioning Questionnaire (Luyten et al, 2017) examines three factors of the construct (i.e., pre-mentalizing modes, interest in mental states, and certainty regarding mental states) using 18 self-reported items (Khoshroo & Seyed Mousavi, 2021). The development of self-regulation from co-regulation with attachment figures (see Erdmann & Hertel, 2019, for a review) suggests parental RF may have implications for later substance use.…”
Section: The Case Of “Olivia”mentioning
confidence: 99%
“…As regards PRF construct, the studies listed below mostly used an interview-based assessment of mentalizing (e.g., RFS [16,18]) while a few studies [20,[28][29][30][31] used the newly developed Parental Reflective Functioning Questionnaire [20] which is easier and more convenient to operate but prone to the tradeoffs of self-report questionnaires. These studies have highlighted the role of PRF in regard to a child's psychopathological symptoms by showing a negative association between good parental mentalizing and child's internalizing and externalizing problems [28,[30][31][32][33][34][35][36][37], and better socio-emotional competencies and fewer socio-emotional problems for the child [31,38]. Other studies have shown a negative association between parental mentalizing and a child's anxiety levels [39] and a positive relationship with a child's mentalizing [40][41][42][43].…”
Section: Parental Mentalizing: Theory and Assessmentmentioning
confidence: 99%